The Analysis Of History Collection System Based On Android Smartphone With Qr Code Using Qr Code Case Study: Museum Lampung - Usman Rizal; Wiwin Susanty; . Sutrisno (International Conference on Engineering and Technology Development (ICETD), 2013)
This scientific writing is to describe and explain the activities that related with using quick respon (QR) qode on collection history so it can be known as the advantages and disadvantages that exist in the system History Collection. The purpose of this analysis is to evaluate the advantages and disadvantages of the use of Quick Response (QR) Code for Collection System History at the museum Lampung as well as to study the QR Code.